2020
DOI: 10.1136/bmjopen-2020-039473
|View full text |Cite
|
Sign up to set email alerts
|

Collaboration between patient organisations and a clinical research sponsor in a rare disease condition: learnings from a community advisory board and best practice for future collaborations

Abstract: Introduction Transparent collaborations between patient organisations (POs) and clinical research sponsors (CRS) can identify and address the unmet needs of patients and caregivers. These insights can improve clinical trial participant experience and delivery of medical innovations necessary to advance health outcomes and standards of care. We share our experiences from such a collaboration undertaken surrounding the SENSCIS® clinical trial (NCT02597933), and discuss its impact during, and legacy beyond, the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…95% had also had undertaken research activity such as: financing, lobby A questionnaire survey was used for evaluating the impact of PI PI may improve lack of financial resources, lack of interest on rare diseases, increase the recruitment rate and registry. Therefore important that researchers must work with Patient-Organizations The study reported that PI is important and could help advance scientific knowledge and therapy, thereby alleviating the personal and societal burden of RDs Described PI in research dissemination 78% reported being involved in disseminated of research, such as doing it available at the web site RDPO websites showed that leaders had compiled information about PI in current research projects and findings PI had increased the use of more relevant research dissemination channels Interviewed leaders gave examples of how this information had led organizational members to develop ideas for further research, which they then used in discussions with researchers or as a basis for awarding research funding Roennow et al [ 36 ]. Collaboration between patient organisations and a clinical research sponsor in a rare disease condition: learnings from a community advisory board and best practice for future collaborations BMJ Open International collaboration Qualitative design with communication of experiences To share our experiences from such a collaboration undertaken surrounding the SENSCIS® clinical trial (NCT02597933), and discuss its impact during, and legacy beyond, the trial Diagnosis: scleroderma / systemic sclerosis 15 patient representatives from Scleroderma patient associations from 10 countries Describes establishment of a community advisory board (CAB): a transparent, multiyear collaboration between the scleroderma patient community and a clinical research sponsor A community advisory board was established where patient offer their expertise to clinical research sponsor to discuss overall program development.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…95% had also had undertaken research activity such as: financing, lobby A questionnaire survey was used for evaluating the impact of PI PI may improve lack of financial resources, lack of interest on rare diseases, increase the recruitment rate and registry. Therefore important that researchers must work with Patient-Organizations The study reported that PI is important and could help advance scientific knowledge and therapy, thereby alleviating the personal and societal burden of RDs Described PI in research dissemination 78% reported being involved in disseminated of research, such as doing it available at the web site RDPO websites showed that leaders had compiled information about PI in current research projects and findings PI had increased the use of more relevant research dissemination channels Interviewed leaders gave examples of how this information had led organizational members to develop ideas for further research, which they then used in discussions with researchers or as a basis for awarding research funding Roennow et al [ 36 ]. Collaboration between patient organisations and a clinical research sponsor in a rare disease condition: learnings from a community advisory board and best practice for future collaborations BMJ Open International collaboration Qualitative design with communication of experiences To share our experiences from such a collaboration undertaken surrounding the SENSCIS® clinical trial (NCT02597933), and discuss its impact during, and legacy beyond, the trial Diagnosis: scleroderma / systemic sclerosis 15 patient representatives from Scleroderma patient associations from 10 countries Describes establishment of a community advisory board (CAB): a transparent, multiyear collaboration between the scleroderma patient community and a clinical research sponsor A community advisory board was established where patient offer their expertise to clinical research sponsor to discuss overall program development.…”
Section: Resultsmentioning
confidence: 99%
“…Roennow et al [ 36 ]. Collaboration between patient organisations and a clinical research sponsor in a rare disease condition: learnings from a community advisory board and best practice for future collaborations…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There has been a gradual shift from a disease-centred to a patient-centred strategy and from a product-led to a patient-led development process [ 18 ]. While generally no direct-to-patient advertising is allowed (except in USA, Hong Kong and New Zealand, with some restrictions) [ 1 ], patient advocacy groups play an important intermediary partner for medical and public affairs [ 19 , 20 ]. Other endeavours, including studying and collecting patient-reported outcomes in clinical and especially real-world studies [ 21 , 22 ], leading tailored disease awareness and patient education campaigns [ 23 , 24 ], real-time diagnostic and treatment analytical support [ 25 ] have helped to not only empower patients but also generate valuable real-world data [ 26 – 29 ].…”
Section: Dynamic Evolving Role Of Medical Affairs Function Before Covid-19 Pandemicmentioning
confidence: 99%